Efficiency Analysis of Local Government Spending of Regencies and Cities in West Java, 2001-2010 - Sihaloho, Estro Dariatno (P2E-LIPI, 2015)
This paper has two objectives. The frst is to estimate technical effciency scores for local government expenditure in regencies and cities in West Java. The second is to analyze the other environmental factors that play animportant role in the technical effciency scores of local government expenditure in the same regencies and cities.This research uses a Data Envelopment Analysis (DEA) method to estimate technical effciency scores and usesa Tobit method for analyzing environmental factors. The DEA method uses capital expenditure per capita,employment of government expenditure per capita, and goods and services expenditure per capita as input anduses Gross Regional Product (GRP) per capita, human capital index (HDI) and road infrastructure length perwide area as output. The Tobit method uses the total of investment credit funds, total labor and total governmentemployment per 1000 civil servants. The results showed that there are many region that have high spendingbut can not achieved the maximum score of effciency. The Tobit estimation shows that the total of investmentcredit funding and total labor have positive and signifcant marginal effects in creating optimal technical effciencyscores. Total government employment per 1000 civil servants has a negative and insignifcant marginal effect onoptimal technical effciency scores.